Acroneuria kirchneri Stark & Kondratieff, 2004 is a synonym of Acroneuria kosztarabi Kondratieff & Kirchner, 1993 (Plecoptera: Perlidae) - Verdone, Chris J.; South, Eric J.; Kondratieff, Boris C. (Zootaxa, 2022)
Acroneuria Pictet, 1841 (Plecoptera: Perlidae) is a genus of stoneflies which presently includes 18 summer emerging Nearctic species. Diagnosis of species relies primarily on male aedeagal setal patterns, details of the ovum chorion, and larval dorsal maculations. Several species are morphologically cryptic in one or more life stages. In 2010, an apparently rare species, A. kosztarabi Kondratieff & Kirchner, 1993, was petitioned for listing under the Endangered Species Act. A status survey conducted in 2016–2017 produced new specimen collections from near the type locality and surrounding areas. Examination of new material and the holotype of A. kirchneri Stark & Kondratieff, 2004 demonstrates that it is a junior subjective synonym of A. kosztarabi. All life stages of A. kosztarabi are redescribed using color photographs and scanning electron microscope photomicrographs. Supporting data include maximum likelihood and pairwise genetic distance analyses based on mitochondrial cytochrome c oxidase subunit I fragment data. Acroneuria kosztarabi, previously known only from the type locality, is now reported from six states in the southeastern United States ranging from central North Carolina to western Tennessee and north to northern Virginia and northern Ohio.